2013
DOI: 10.1073/pnas.1215902110
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal regulation of PKA and Rac signaling

Abstract: Activated G protein-coupled receptors (GPCRs) and receptor tyrosine kinases relay extracellular signals through spatial and temporal controlled kinase and GTPase entities. These enzymes are coordinated by multifunctional scaffolding proteins for precise intracellular signal processing. The cAMP-dependent protein kinase A (PKA) is the prime example for compartmentalized signal transmission downstream of distinct GPCRs. A-kinase anchoring proteins tether PKA to specific intracellular sites to ensure precision an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 55 publications
5
55
0
Order By: Relevance
“…PKA activation resulted in PAK-dependent phosphorylation of PREX1, suggesting that PKA is upstream of PAKs. A recent study showed that Rac binds to a PKA regulatory subunit and that PKA phosphorylates and activates PAK, setting up a model where PKA binds Rac-GTP to help in the stimulation of PAK and its downstream signals (45). It is also important to note that PREX1 is both activated by isoproterenol in cells and negatively regulated by PKA in vitro (10,31,32,46).…”
Section: Discussionmentioning
confidence: 99%
“…PKA activation resulted in PAK-dependent phosphorylation of PREX1, suggesting that PKA is upstream of PAKs. A recent study showed that Rac binds to a PKA regulatory subunit and that PKA phosphorylates and activates PAK, setting up a model where PKA binds Rac-GTP to help in the stimulation of PAK and its downstream signals (45). It is also important to note that PREX1 is both activated by isoproterenol in cells and negatively regulated by PKA in vitro (10,31,32,46).…”
Section: Discussionmentioning
confidence: 99%
“…Rluc bioluminescence signals were integrated for 10 s following addition of the Rluc substrate benzylcoelenterazine to intact cells (5 μM; NanoLight). For immunoblot analyses, anti-Renilla luciferase antibodies to detect either F[1]-fused (Millipore; MAB4410) or F[2]-fused (Millipore; MAB4400) hybrid proteins were used (23,24).…”
Section: Methodsmentioning
confidence: 99%
“…Rluc-based PCA sentinels have been designed and used to study the dynamics of PPIs in vivo (23,24). An advantage of this assay is that it reports absolute values of protein-complex formation in real time.…”
Section: A Library Of Pyridine Compounds Yields Effective Inhibitors mentioning
confidence: 99%
“…To identify the specific amino acid residues of Gpr161 that are responsible for RIα binding, we used a peptide array assay. Overlapping 25-mer peptides derived from the human Gpr161-CT sequence were spotted onto a membrane and overlaid with recombinant RIα-his 6 , as previously described (27,28). In the Gpr161-CT we identified only one possible binding site for RIα.…”
Section: -528mentioning
confidence: 99%